Tantangan Intellectual Movement Community (IMC) sebagai Communities of Practice (CoP) di IAIN Jember dan Peran Pustakawan dalam mendukung Keberhasilan IMC - Nurhayati Aisatun (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2018)
As the part of knowledge management, Community of Practice (CoP) is the strategic media through knowledge sharing for organization success. This research focus on the effectiveness of Intellectual Movement Community (IMC) IAIN Jember based on four challenging variables, it explains the relationship between variable and librarian role supporting to achieve the success of a community. The method that use in this research is mixed method and use concurrent triangulation model design. The population is IMC members and as the sample role too. The data collection use questionnaire with Likert scale, documentation and interview. The result of the research show that the correlation between four variables toward IMC community success are personal challenge correlation has the highest percentage (92,3%), community challenge has the lowest correlation (87,1%). Those variables show the correlation toward IMC community’s success degree amount 89,4%. The correlation between variable show that management challenging has the positive correlation and strong toward technical challenge (71,6%), it is also strong enough toward community challenge (42,5%) and personal challenge (49,2%). The correlation of community challenging and personal challenging also has the strong correlation (42,7%). However, the correlation of technical challenging toward community challenging (36,3%) and personal challenging (19,3%) show the negative correlation or weak. This research also found some internal and external factors that make librarian did not give the optimal contribute in supporting IMC success.